2021
DOI: 10.1515/epoly-2021-0021
|View full text |Cite
|
Sign up to set email alerts
|

Properties of a bovine collagen type I membrane for guided bone regeneration applications

Abstract: Dental implant treatment requires an available bone volume in the implantation site to ensure the implant’s mechanical stability. When the bone volume is insufficient, one must resort to surgical means such as guided bone regeneration (GBR). In GBR surgery, bone grafts and membranes are used. The objective of this work is to manufacture and characterize the in vitro and in vivo properties of resorbable collagen type I membranes (Green Membrane®) for GBR. Membrane surface morphology was characterized by SEM and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 40 publications
0
10
0
1
Order By: Relevance
“…Brum et al [ 7 ] analyzed the cytotoxic, ultrastructural characteristics of a 1-mm thick non-reticulated collagen membrane indicated for guided bone regeneration surgery. The authors observed that the morphology of the membrane promotes an increase in the differentiation of osteocytes [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Brum et al [ 7 ] analyzed the cytotoxic, ultrastructural characteristics of a 1-mm thick non-reticulated collagen membrane indicated for guided bone regeneration surgery. The authors observed that the morphology of the membrane promotes an increase in the differentiation of osteocytes [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Brum et al [ 7 ] analyzed the cytotoxic, ultrastructural characteristics of a 1-mm thick non-reticulated collagen membrane indicated for guided bone regeneration surgery. The authors observed that the morphology of the membrane promotes an increase in the differentiation of osteocytes [ 7 ]. A systematic review and meta-analysis work on guided bone regeneration concluded that the association of the membrane improves the performance of the biomaterial and promotes an increase in the survival of implants [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collagen accounts for roughly 95% of the organic matrix in bone tissue and plays important roles in a variety of osteoblast activities [ 19 ], such as tissue repair through the activation of platelets via the integrin α2β1-binding domain [ 20 ]. These molecules also function as mediators of osteoblast cell responses [ 21 ], including in proliferation and migration during the healing process [ 22 , 23 , 24 ] as well as in secretion of the extracellular matrix (ECM) and osteoblast differentiation [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, nanotechnology has been improving the bioactive properties of hydroxyapatite in relation to its crystals, resulting in a better response in association with nanocrystals than with thicker crystals [6]. The crystallinity is the property responsible for the biomaterial remaining for more or less time in the body, and with these advances in the way the crystals are manufactured, it is possible to control not only the reabsorption time but also the replacement of the material more efficiently [7][8][9].…”
Section: Introductionmentioning
confidence: 99%